Mining the jewels of the cortex's crowning mystery. (August 2020) - Ibrahim, Leena A; Schuman, Ben; Bandler, Rachel; Rudy, Bernardo; Fishell, Gord
Highlights: Layer 1 of the cortex consists of axons, dendrites of pyramidal neurons, as well as resident inhibitory interneurons (L1 interneurons). L1 interneurons originate from the caudal ganglionic eminence (CGE) and a subset arises from the preoptic area (POA). There are 4 major subtypes of L1 interneurons, with diverse morphology, physiology, and molecular profiles. L1 interneurons respond to sensory, cross-modal, neuromodulatory, and higher order top down inputs. Abstract : Neocortical Layer 1 consists of a dense mesh of excitatory and inhibitory axons, dendrites of pyramidal neurons, as well as neuromodulatory inputs from diverse brain regions. Layer 1 also consists of a sparse population of inhibitory interneurons, which are appropriately positioned to receive and integrate the information from these regions of the brain and modulate cortical processing. Despite being among the sparsest neuronal population in the cortex, Layer 1 interneurons perform powerful computations and have elaborate morphologies. Here we review recent studies characterizing their origin, morphology, physiology, and molecular profiles, as well as their connectivity and in vivo response properties.